Kharchinskii and Zarechnyi volcanoes, unique centers of Late Pleistocene magnesian basalts in Kamchatka: Composition of erupted rocks - Volynets O.N.; Melekestsev I.V.; Ponomareva V.V.; Yogodzinski J.M. (My University, 1999)
Most of the Kharchinskii and Zarechnyi products, as well as those of the Kharchinskii cinder cones, are magnesian rocks. Mineralogical data suggest that both the basaltic and the andesitic magma were rich in water (≥3-4 and >6-7 wt., respectively) and crystallized at high oxygen fugacity (2.0-2.5 orders of magnitude higher than the NNO buffer). These features, coupled with the geochemical characteristics of these basalts and andesites, indicate that they are similar to the rocks of Shiveluch, a volcano also located on the northern flank of the Northern volcanic group, but differ from the rocks of the other volcanoes of this group which are located further south. The Kharchinskii, Zarechnyi, and Shiveluch magnesian basalts differ from the rocks of the Klyuchevskoi volcano and Tolbachik lava field by their higher K, Ba, Sr and lower Ca, Sc, Yb contents at higher La/Yb, Ni/Sc, and La/Ta ratios, while their initial magmas were more hydrous and more oxidized.
Keywords: 38.37.25 Вулканология; Харчинский; Заречный